Novel metabolites to improve glomerular filtration rate estimation - Xinghua Guo; Hongquan Peng; Peijia Liu; Leile Tang; Jia Fang; ChiWa AoIeong; Tou Tou; Tsungyang Tsai; Xun Liu (Karger Publishers, 2023)
Introduction: The glomerular filtration rate (GFR) is crucial for chronic kidney disease (CKD) diagnosis and therapy. Various studies have sought to recognize ideal endogenous markers to improve the estimated GFR (eGFR) for clinical practice. To screen out potential novel metabolites related to GFR (mGFR) measurement in CKD patients from the Chinese population, we identified more biomarkers for improving GFR estimation. Methods: Fifty-three CKD participants were recruited from the third affiliated hospital of Sun Yat-sen University in 2020. For each participant, mGFR was evaluated by utilizing the plasma clearance of iohexol and collecting serum samples for untargeted metabolomics analyses by Ultrahigh Performance Liquid Chromatography-Tandem Mass Spectroscopy (UPLC-MS/MS). All participants were divided into four groups according to mGFR. The metabolite peak area data were uploaded to MetaboAnalyst5.0 for one-way ANOVA, principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA) and confirmed the metabolites whose levels increased or decreased with mGFR and Variable Importance in Projection (VIP) values>1. Metabolites were ranked by correlation with the original values of mGFR, and metabolites with a correlation coefficient>0.8 and VIP >2 were identified. Results: We screened out 198 metabolites that increased or decreased with mGFR decline. After ranking by correlation with mGFR, the top 50 metabolites were confirmed. Further studies confirmed the 10 most highly correlated metabolites. Conclusion: We screened out the metabolites that increased or decreased with mGFR decline in CKD patients from the Chinese population, and 10 of them were highly correlated. They are potential novel metabolites to improve GFR estimation.